THE EFFECT OF LIMITED LEARNING (MICROTEACHING) ON THE TEACHING ABILITY OF IPS TADRIS STUDENTS STATE ISLAMIC UNIVERSITY OF NORTH SUMATRA - Susanti, Eka; Perkasa, Ripho Delzy; Marsa, Yummi Jumiati (Universitas Indraprasta PGRI, 2025)
This study was conducted to determine how much influence limited learning (microteaching) has on the teaching ability of students of the Tadris IPS study program. This type of research is quantitative research. The population of this study consisted of 3 classes totaling 105 people, the sample of this study was taken by random sampling by drawing classes. Data analysis using normality test, regression hypothesis test. The results of the study showed a significant influence of limited learning (microteaching) on the teaching ability of Tadris IPS students. Based on the results of the regression analysis, the significance results showed p = 0.000 with the criteria p <0.05, it can be stated that there is an influence between microteaching learning on the teaching ability of students of the Tadris IPS study program. Based on the results of the simple linear regression analysis, it can be seen that there is a positive influence that can be proven through the results of the linear regression analysis predicted using the regression equation Y = a + bX or Y = 354.675 + 0.723X. So from the equation it can be explained that the positive constant value is 354.675 with a regression coefficient of X of 0.723, which means that Microteaching Learning (X) has increased by 1 unit, so the value of the teaching ability variable has increased by 1 unit by 0.723. This means that there is a positive influence between microteaching learning and teaching ability.